2016
DOI: 10.1111/dom.12784
|View full text |Cite
|
Sign up to set email alerts
|

Increased liver fat and glycogen stores after consumption of high versus low glycaemic index food: A randomized crossover study

Abstract: Compared with an LGI diet, a 1-week HGI diet increased hepatic fat and glycogen stores. This may have important clinical relevance for dietary interventions in the prevention and management of non-alcoholic fatty liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 35 publications
2
53
0
1
Order By: Relevance
“…Our results extend existing evidence [47,48] suggesting that a higher-GI diet and an increased intake of higher-GI-CHO are both of longer-term relevance for hepatic steatosis and that these associations are specific to evening intakes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results extend existing evidence [47,48] suggesting that a higher-GI diet and an increased intake of higher-GI-CHO are both of longer-term relevance for hepatic steatosis and that these associations are specific to evening intakes.…”
Section: Discussionsupporting
confidence: 89%
“…Two studies, although heterogeneous in their methods (intervention vs observational study, extreme (dietary GI 32 vs. 84) vs. habitual low/high-GI diets and determination of liver steatosis severity by 1 H magnetic resonance spectroscopy and liver ultrasonography scanning, respectively), suggest that the dietary GI may be related to liver function [47,48]. However, it should be noted that imaging methods as used in these studies are time- and cost-intensive and therefore often infeasible in observational studies.…”
Section: Discussionmentioning
confidence: 99%
“…In recent times, it has gained a wider application, and assessing the glycaemic index and glycaemic load of diets has been included in a number of prospective cohort studies which are summarised in the SACN report [1]. This has led to several randomised controlled trials of potential benefits of lower glycaemic index diets, including a recent study of our own (Bawden et al [25]) which showed that healthy non-obese young men consuming a high glycaemic index diet for 7 days showed an increase in liver fat content, whereas 7 days on a low glycaemic index diet was accompanied by a small decrease in liver fat. In this study, the dietary GI was estimated on the basis of the GI tables provided by Brand-Miller’s group [26].…”
Section: Should We Be More Concerned About Dietary Glycaemic Charactementioning
confidence: 99%
“…Variations in response to high versus low glycaemic index breakfasts have also been observed (Fig. 2b) [59]. In a recent 1-week dietary intervention crossover study, fasted glycogen stores in the liver were significantly elevated after a high glycaemic index diet when compared with low glycaemic index diet.…”
Section: Mrs Measurements Of Liver Glycogenmentioning
confidence: 57%